EXPLORING THE INFLUENCE OF CHATGPT ON INFORMATION NEEDS AND SEEKING BEHAVIOR OF LIBRARY USERS AT MGCU, MOTIHARI, BIHAR. - Kumar, Prafful; Gautam, Awadhesh Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the impact of ChatGPT on the information needs and seeking behavior of library users at Mahatma Gandhi Central University (MGCU) in Motihari, Bihar. As artificial intelligence language models like ChatGPT become increasingly accessible, it is crucial to understand how they are influencing traditional information-seeking practices in academic settings. Through a mixed-methods approach combining surveys, interviews, and usage data analysis, this research examines how MGCU library users are integrating ChatGPT into their information-seeking processes, its effects on their research strategies and library resource utilization, and implications for library services. The findings reveal that while ChatGPT is widely used among students and faculty for quick information retrieval and ideation, it has not replaced in-depth library research. However, it has shifted user expectations around speed and convenience of information access. The study provides insights to help academic libraries adapt their services and information literacy programs to effectively support users in the age of AI-assisted information seeking.